ANTI-INFLAMMATORY EFFECT OF ZINGIBER OFFICINALE ON SPRAGUE DAWLEY RATS - Hassan, Ndanusa Abdullahi; Karunakaran, Rohini; A, Uma Sankar; Aye, Khin Mar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: To investigate the anti-inflammatory effect of aqueous extract of Zingiber officinale on carrageenan-induced inflammation on Sprague Dawley (SD) rats. Methods: SD rats were divided into six of five groups and allowed to acclimatize for 1 week. Inflammation was induced on the animal by injecting the right hand paw with carrageenan (0.1 ml of 1%). Group 1 was given normal saline and served as a control. Group 2 was fed with food and water and served as the carrageenan control. Group 3 was given 200 mg/kg aqueous extract of ginger, Group 4 with 400 mg/kg aqueous extract of ginger, and Group 5 with 150 mg/kg diclofenac sodium (reference drug for inflammation). Results: The paw edema in carrageenan-induced SD rats was considerably reduced by treating with 400 mg/kg aqueous ginger extracts when compared to the untreated SD rats (p<0.001). Conclusion: This study indicates that aqueous extract of Z. officinale possesses anti-inflammatory properties. Keywords: Anti-inflammatory, Sprague Dawley rats, Zingiber officinale, Carrageenan, Edema